2021
DOI: 10.1164/rccm.202012-4461oc
|View full text |Cite
|
Sign up to set email alerts
|

Increased Angiotensin-Converting Enzyme 2 and Loss of Alveolar Type II Cells in COVID-19–related Acute Respiratory Distress Syndrome

Abstract: ML contributed to data collection, performed technical analysis and extensively revised the manuscript CB contributed to data collection, performed image analysis and extensively revised the manuscript.DH contributed to the acquisition of tissue material and to technical analysis and extensively revised the manuscript.GS contributed to the acquisition of the tissue material and extensively revised the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 52 publications
5
60
0
1
Order By: Relevance
“…The authors suggested that hrsACE2 could block the systemic spread of the virus from the lung to other organs [ 30 ]. One previous study has demonstrated a significant increase in lung endothelial cell immunostaining for ACE2 and for serum ACE2 levels in 15 COVID-19 patients with ARDS and 13 non-COVID-19 patients with ARDS compared to control tissues from patients who had a lobectomy for lung cancer [ 31 ]. This suggests that differences in sACE2 may reflect the presence of COVID-19-induced ARDS, which reversed over time/with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that hrsACE2 could block the systemic spread of the virus from the lung to other organs [ 30 ]. One previous study has demonstrated a significant increase in lung endothelial cell immunostaining for ACE2 and for serum ACE2 levels in 15 COVID-19 patients with ARDS and 13 non-COVID-19 patients with ARDS compared to control tissues from patients who had a lobectomy for lung cancer [ 31 ]. This suggests that differences in sACE2 may reflect the presence of COVID-19-induced ARDS, which reversed over time/with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A logical explanation would be the previous observation that COVID-19 patients display reduced ACE levels [ 9 11 ]. This is due to the fact that severe lung injury (as occurring in severe COVID-19 patients) induces endothelial dysfunction and loss of pulmonary ACE expression [ 11 , 12 ]. Here, it is important to note that the majority of ACE is expressed on the surface of endothelial cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 patients display elevated soluble ACE2 levels [ 4 – 8 ], demonstrating that virus infectivity is accompanied by ACE2 shedding. At the same time, serum ACE levels are decreased in COVID-19 patients [ 9 11 ], with the greatest drop occurring in the most severe cases. This parallels the observation that lung injury, as occurring in acute respiratory distress syndrome (ARDS), results in diminished pulmonary ACE activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an elevated level of Ang-II was found in patients with H5N1 or H7N9 infection, and these elevated levels were related to the severity of the pulmonary injury [52]. Gerard et al [53] investigated the expression and distribution of ACE2 in COVID-19 and showed that the expression of ACE2 increased in lung tissues, serum, and endothelial cells but decreased in alveolar epithelial cells (AT2). Asaka et al [54] explored the pathogenicity of COVID-19 and found that CAG-hACE2 mice were susceptible to SARS-CoV-2 and the levels of cytokines and chemokines increased, resulting in acute lung injury, while injecting the plasma of immunized mice could reduce the mortality of mice.…”
Section: Ace2 and Sars-cov-2 In Alimentioning
confidence: 99%